Disability due to ocular complications of diabetes mellitus in Ukraine (Ukrainian Journal of Ophthalmology, 2025)
Background: Diabetes mellitus (DM) is a global epidemic. According to reports from the WHO, DM patients have a significantly shorter life span compared to general population, and DM is among the three diseases with the highest risk of disability and mortality.Purpose: To investigate the rates of disability due to ocular complications of DM in Ukraine for the time period from 2004 to 2018.Results: The prevalence of DM in Ukraine was increasing during this period. The annual prevalence of individuals certified as having a DM-induced disability for the first time was relatively stable during 2004 through 2018 and was 1.5 per 10,000 of adult population in 2018. The annual prevalence of individuals certified as having a diabetic retinopathy (DR)-induced visual disability for the first time per 10,000 of adult population was 0.19 in 2018, and varied substantially during the period from 2004 to 2018, with a minimum of 0.13 in 2006 and 2015, maximal values of 0.22 and 0.20 in 2010 and 2015, respectively, and a general tendency to increase. During the period, changes in the prevalence of DR-induced disability varied among Ukrainian regions differing in geographical aspects. The proportion of blind and visually impaired (i.e., severely and moderately disabled, respectively) among individuals certified as having a DR-induced visual disability was higher than that among total individuals certified as having a visual disability for the first time; this indicates that the pathology is severe. The level of accumulated disability due to ophthalmic diabetes in Ukraine increased almost 2.5-fold during the last 15 years.
Keywords: diabetes mellitus; diabetic retinopathy; blindness; disability